Pemanfaatan Canva Sebagai Media Perancangan Grafis - Avril Hs Adila Anugrah; Lukman Hakim Alfaridzi; Claudia Laurent (Institut Nalanda, 2023)
Canva is an online design program application that provides various tools or editing tools to create various graphic designs easily without having to design them from scratch. This research is aimed at providing a solution for using the Canva application as a graphic design medium for novice designers and online marketers. This approach uses a media understanding theory approach. As well as using a qualitative descriptive approach to interpret existing phenomena. The primary data collection process was carried out through in-depth interviews. The results of this research describe that the use of Canva as a graphic design medium is able to provide ease of use, increase designer creativity and produce graphic design content with new innovations.